2022
DOI: 10.1007/s00415-022-11401-7
|View full text |Cite
|
Sign up to set email alerts
|

Exome-based gene panel analysis in a cohort of acute juvenile ischemic stroke patients:relevance of NOTCH3 and GLA variants

Abstract: Background Genetic variants are considered to have a crucial impact on the occurrence of ischemic stroke. In clinical routine, the diagnostic value of next-generation sequencing (NGS) in the medical clarification of acute juvenile stroke has not been investigated so far. Material and methods We analyzed an exome-based gene panel of 349 genes in 172 clinically well-characterized patients with magnetic resonance imaging (MRI)-proven, juvenile (age ≤ 55 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Among the 5 males with pathogenic variants, 3 exhibited the Type 1 phenotype while 2 displayed the Type 2 phenotype. Similarly, a prevalence of 1.11% of patients with FD was found in females (n = 23), but when the benign variants were excluded, only 3 presented pathogenic variants with the Type 1 phenotype and the actual prevalence dropped to 0.14%, similar to that in males [76] . The authors found that most FD patients identified in stroke clinics had the Classic phenotype and, therefore, should have been diagnosed earlier by their pediatricians and family doctors [76] .…”
Section: Screening Of Fd In Patients With Strokementioning
confidence: 81%
See 1 more Smart Citation
“…Among the 5 males with pathogenic variants, 3 exhibited the Type 1 phenotype while 2 displayed the Type 2 phenotype. Similarly, a prevalence of 1.11% of patients with FD was found in females (n = 23), but when the benign variants were excluded, only 3 presented pathogenic variants with the Type 1 phenotype and the actual prevalence dropped to 0.14%, similar to that in males [76] . The authors found that most FD patients identified in stroke clinics had the Classic phenotype and, therefore, should have been diagnosed earlier by their pediatricians and family doctors [76] .…”
Section: Screening Of Fd In Patients With Strokementioning
confidence: 81%
“…In recent years, significant improvement was made in the genotype-phenotype correlation of young patients with stroke included in screening studies of FD, and as a consequence, a lower prevalence of 0.1%-0.3% was estimated [75,76] . This prevalence may be higher in young patients with either cryptogenic or recurrent stroke [75] .…”
Section: Screening Of Fd In Patients With Strokementioning
confidence: 99%
“…Among the 3941 studies identified from the initial database search, 110 met the inclusion criteria and were analyzed for the systematic review and meta-analysis (Figure 1; Table SI). Among the included studies, 26 reports screened patients with left ventricular hypertrophy (LVH)/hypertrophic cardiomyopathy (HCM), 12–37 38 patients with end-stage renal disease (ESRD)/chronic kidney disease (CKD), 38–74 25 patients with stroke patients, 75–99 15 patients with newborns, 100–114 3 patients with small-fiber neuropathy patients, 115–117 and 3 patients with atrioventricular block or sinus node dysfunction requiring pacemaker implantation 118–120 (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-five studies performing screening in patients with stroke met the inclusion criteria, 75–99 providing data on the prevalence of FD among 15 295 patients screened.…”
Section: Resultsmentioning
confidence: 99%
“…21 The NOTCH3 p.R75P mutation has been identified in patients with CADASIL in South Korea and China, but not in non-East Asian people, such as British, French, Finnish, Swedish, German, and Brazilian, indicating that different NOTCH3 mutations are associated with distinct CADASIL phenotypes between East Asian and white European populations. 17,18,[22][23][24][25][26] Additionally, the cysteine-altering NOTCH3 p.R544C mutation was evaluated for its association with ICH, because it is an East Asian-specific mutation, but the result was negative. 6 Intriguingly, the first report of the NOTCH3 p.R75P mutation from South Korea showed a high frequency of this mutation among CADASIL patients with CMB.…”
Section: Introductionmentioning
confidence: 99%